2022
DOI: 10.33751/jsep.v6i2.5855
|View full text |Cite
|
Sign up to set email alerts
|

Science Learning with The Qur'an and Hadith Through Audiovisual Media (Video) to Improve Concept Mastery and Religious Attitude

Abstract: This study aims to improve students' concept mastery and religious attitudes in science learning with the Quran and Hadith contents through audiovisual media (video). The research design was quasi-experimental, with experimental and control classes as the research subjects. Data were collected using a test to measure students' concept mastery and religious attitudes with 30 questions, an observation sheet, and a questionnaire with 22 questions. The measurement results of the two test forms were analyzed in N-G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…A recent study investigated the use of audiovisual media in teaching Quran and Hadith to enhance students' understanding of concepts and their religious attitudes. The study found that multimedia approaches were effective in improving student learning outcomes and motivation (Annas & Permana, 2022). A recent study conducted by Rahmiati et al (2021) examined the development of a social enquiry model for Quran and Hadith learning.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study investigated the use of audiovisual media in teaching Quran and Hadith to enhance students' understanding of concepts and their religious attitudes. The study found that multimedia approaches were effective in improving student learning outcomes and motivation (Annas & Permana, 2022). A recent study conducted by Rahmiati et al (2021) examined the development of a social enquiry model for Quran and Hadith learning.…”
Section: Introductionmentioning
confidence: 99%